2012
DOI: 10.1007/s10561-012-9352-y
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the edentulous mandible with fresh frozen bone grafts and implants: a 4-year report of a prospective clinical study

Abstract: Allogen bones from tissue bank are often used in dentistry although the data analyzing the long-term success in mandible are scarce. This study evaluated by computed tomography scans (CTS) the bone resorption around the implants installed on fresh frozen bone (FFB) previously grafted, after 4 years of occlusal rehabilitation. Six subjects were grafted with blocks in posterior mandible using FFB. After 6 months, 27 implants were placed and after further 4 months the prostheses were delivered. Following 4 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 12 publications
0
9
0
7
Order By: Relevance
“…We obtained an implant placement success rate of 96.6% in an evaluation period of 15.3-28.7 months. Other studies have shown a similar high success rate of osseointegration, varying from 95.3 to 100% (Holmquist et al 2008;Contar et al 2009;Morelli et al 2009;Nissan et al 2011a,b;Novell et al 2012;Pimentel et al 2014). However, among those previous studies, some (Holmquist et al 2008;Contar et al 2009;Novell et al 2012) studies used this technique on the maxilla; thus, it is difficult to make a direct comparison, as maxillary bone has greater vascularization and the FFB has a greater chance to integrate at the recipient site.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…We obtained an implant placement success rate of 96.6% in an evaluation period of 15.3-28.7 months. Other studies have shown a similar high success rate of osseointegration, varying from 95.3 to 100% (Holmquist et al 2008;Contar et al 2009;Morelli et al 2009;Nissan et al 2011a,b;Novell et al 2012;Pimentel et al 2014). However, among those previous studies, some (Holmquist et al 2008;Contar et al 2009;Novell et al 2012) studies used this technique on the maxilla; thus, it is difficult to make a direct comparison, as maxillary bone has greater vascularization and the FFB has a greater chance to integrate at the recipient site.…”
Section: Discussionmentioning
confidence: 75%
“…Magnification, 109. Macedo et al 2012;Chiapasco et al 2013;Pimentel et al 2014). This study was designed to evaluate whether corticomedullary grafts in FFB blocks could be used for bone augmentation and maintenance of graft volume in atrophied posterior human mandibles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Allogeneic bone is considered a second line treatment option for grafting, due mainly to its osteoconductive properties (15) and high implant survival rates (16,17). The antigenicity and immune response associated with allogenic bone grafts remain poorly understood (8,18) and so, largely controversial.…”
Section: Discussionmentioning
confidence: 99%
“…O risco possível de transmissão de doenças é praticamente nulo devido às técnicas atuais de captação, rastreamento, processamento e quarentena. Após um período mínimo de armazenamento de 6 meses a -80ºC, o tecido ósseo somente será liberado, caso não haja contraindicações oriundas de possíveis resultados da rastreabilidade (Dodd et al, 1988;Tomford, 2000;Giannoudis et al, 2005;Heyligers e Klein-Nulend, 2005;Pimentel et al, 2014). Outro fator importante é o resfriamento do osso alógeno humano a uma temperatura menor que -20ºC que diminui, consideravelmente, a antigenicidade (Dodd et al, 1988;Contar et al, 2009).…”
Section: Introductionunclassified